Research on Modeling Method of Gas Turbine Inlet Pressure Loss - Yunfeng JIN; Chao LIU; Gaofeng DENG; Yunlong GUAN; Xin TIAN; Haizhou HUANG; Dongxiang JIANG (发电技术)
In order to ensure the safe and economic operation of gas turbine, it is of great significance to control the inlet pressure loss in the inlet filtration system. This paper divided the inlet pressure loss into two parts: pipeline flow loss and filter pressure loss. The function relationship between the inlet pressure loss and air velocity was established based on the mechanism analysis, and correction factors were introduced to consider the influence of external atmospheric environment and filter degradation. Then, the model was verified through the performance experiment of air filter and the collection of field data, which shows that the relationship between inlet pressure loss and the influencing factors is in good agreement with the model. Finally, by combining the thermodynamic system model of gas turbine, the influence of inlet pressure loss on gas turbine performance was analyzed. The results show that when the filter is near the service life, the negative effect of abnormal environmental factors on the output power of gas turbine is more obvious than that of the new filter.